New species and records of Nandeva Wiedenbrug, Reiss et Fittkau (Chironomidae: Chironominae) - Andersen, Trond; Sæther, Ole A.; Contreras-Ramos, Atilano (Zootaxa, 2011)
Nandeva digitifer sp. n. from Chile is described and figured as male and female and N. verruculata sp. n. from Brazil as male. The female of N. latiloba Sæther et Roque is also described and figured and new Neotropical records of N. latiloba, N. strixinorum Sæther et Roque and N. tropica Wiedenbrug, Reiss et Fittkau are given. The female of N. fittkaui Cranston is re-examined. New generic diagnosis and description are given for the imagines. Some character states from previous parsimony analyses are corrected and new analyses performed indicating Nandeva as part of Tanytarsini or as part of the sister group to Tanytarsini.